Reconfiguring Digital Business Models to Enter the Japanese Market - Ojala, Arto; Baber, William W. (Routledge, 2023)
This chapter analyses the reconfiguration of digital business models of firms when entering the Japanese market. Digitalisation of products and services has led to situation where firms must constantly reconfigure, adjust and innovate their business models for new market conditions predominately foreign. Existing business model studies provide very limited insight as to how business models might change and evolve over time when a firm enters an unknown foreign market. A longitudinal study encompassing 10 years of a Finnish digital service provider's market entry experiences with the Japanese market is presented and analysed. The empirical data, presented in the chapter, are built on 13 in-depth face-to-face interviews conducted in a ten-year period between 2011 and 2021. Based on the empirical data, the authors determine how and why the case firm's digital business model changed over time and how the studied firm found a lucrative business model for the firm's operations in Japan. The findings indicate that the case firm continuously reconfigured its business model. The findings have clearly highlighted that networking based on personal relationships, ability to innovate new digital services based on customer requirements, and the capability to change the business model constantly have played key roles for thriving in the Japanese market.
Keywords: business model; business model innovation; Digital services; Platform; foreign market entry; internationalisation; Japan; fi=Kansainvälinen liiketoiminta|en=International Business|